Genealogy of conservative religious movements and politics in México - de la Torre Castellanos, Renée (2020)
The main objective of this work is to attend to the changes that conservatism has undergone throughout recent history, breaking down its unitary vision to present different modalities of conservatism. Among these changes we distinguish: 1) the displacement of their demands and the redefinition of the threatening others; 2) changes in the agents that represent conservatism; 3) transformations in strategies and their areas of action; 4) recomposition of alliances and opposition blocks.